Unsuspected and extensive transmission of a drug-susceptible Mycobacterium tuberculosis strain - Vitoria Ma Asunción (BMC Pulmonary Medicine, 2009)
Abstract Background A large and unsuspected tuberculosis outbreak involving 18.7% of the total of the tuberculosis cases studied, was detected in a population-based molecular epidemiological study performed in Zaragoza (Spain) from 2001 to 2004. Methods The Mycobacterium tuberculosis drug-susceptible strain, named MTZ strain, was genetically characterized by IS6110-RFLP, Spoligotyping and by MIRU-VNTR typing and the genetic patterns obtained were compared with those included in international databases. The characteristics of the affected patients, in an attempt to understand why the MTZ strain was so highly transmitted among the population were also analyzed. Results The genetic profile of the MTZ strain was rare and not widely distributed in our area or elsewhere. The patients affected did not show any notable risk factor for TB. Conclusion The M. tuberculosis strain MTZ, might have particular transmissibility or virulence properties, and we believe that greater focus should be placed on stopping its widespread dissemination.